2022
DOI: 10.1111/jth.15844
|View full text |Cite
|
Sign up to set email alerts
|

The NO/cGMP/PKG pathway in platelets: The therapeutic potential of PDE5 inhibitors in platelet disorders

Abstract: Platelets are the “guardians” of the blood circulatory system. At sites of vessel injury, they ensure hemostasis and promote immunity and vessel repair. However, their uncontrolled activation is one of the main drivers of thrombosis. To keep circulating platelets in a quiescent state, the endothelium releases platelet antagonists including nitric oxide (NO) that acts by stimulating the intracellular receptor guanylyl cyclase (GC). The latter produces the second messenger cyclic guanosine‐3′,5′‐monophosphate (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 117 publications
(223 reference statements)
0
10
0
Order By: Relevance
“…Nitric oxide is a key signaling molecule in endothelium to act as vasodilator factor, generated by nitric oxide synthase (NOS) ( 78 ). Endothelial production of NO can inhibit multiple events during AS, such as inhibiting ECs activation, macrophage infiltration ( 79 ), foam cell formation/migration ( 80 ), platelet aggregation ( 81 ), inflammation ( 82 ), thrombosis ( 83 ), vascular wall remodeling ( 84 ), and mediating vasodilation ( 85 ). The mechanism of Hcy disturbance of NO synthesis is relatively complex, asymmetric dimethylarginine (ADMA) plays an important role in it, which is an endogenous inhibitor of NOS.…”
Section: Mechanism Of Endothelial Injury By Homocysteinementioning
confidence: 99%
“…Nitric oxide is a key signaling molecule in endothelium to act as vasodilator factor, generated by nitric oxide synthase (NOS) ( 78 ). Endothelial production of NO can inhibit multiple events during AS, such as inhibiting ECs activation, macrophage infiltration ( 79 ), foam cell formation/migration ( 80 ), platelet aggregation ( 81 ), inflammation ( 82 ), thrombosis ( 83 ), vascular wall remodeling ( 84 ), and mediating vasodilation ( 85 ). The mechanism of Hcy disturbance of NO synthesis is relatively complex, asymmetric dimethylarginine (ADMA) plays an important role in it, which is an endogenous inhibitor of NOS.…”
Section: Mechanism Of Endothelial Injury By Homocysteinementioning
confidence: 99%
“…NO regulates cGMP levels and the cGMP inhibitory effects predominantly depend on the PKG, the major effector of cGMP signaling in the cardiovascular system [ 49 , 50 , 51 , 52 , 53 ] ( Figure 1 ).…”
Section: Some Aspects Of Platelet Activationmentioning
confidence: 99%
“…7 Interestingly, several preclinical studies have shown beneficial effects of PDE5 inhibitors in the treatment of diseases where platelets play essential roles. 7…”
mentioning
confidence: 99%
“…6,7 Understanding how cGMP degradation contributes to platelet function is clinically relevant as selective PDE5 inhibitors (e.g., sildenafil and tadalafil) are used for the treatment of erectile dysfunction, pulmonary arterial hypertension, and certain lower urinary tract symptoms. 7 Interestingly, several preclinical studies have shown beneficial effects of PDE5 inhibitors in the treatment of diseases where platelets play essential roles. 7 In this issue of Thrombosis and Haemostasis, Gui et al provide genetic evidence of the role of PDE5A in platelet function and thrombus formation using a constitutive KO mouse model.…”
mentioning
confidence: 99%
See 1 more Smart Citation